The impact of post-fall huddles on repeat fall rates and perceptions of safety culture: a quasi-experimental evaluation of a patient safety demonstration project - Katherine J. Jones; John Crowe; Joseph A. Allen; Anne M. Skinner; Robin High; Victoria Kennel; Roni Reiter-Palmon (BMC, 2019)
Abstract Background Conducting post-fall huddles is considered an integral component of a fall-risk-reduction program. However, there is no evidence linking post-fall huddles to patient outcomes or perceptions of teamwork and safety culture. The purpose of this study is to determine associations between conducting post-fall huddles and repeat fall rates and between post-fall huddle participation and perceptions of teamwork and safety culture. Methods During a two-year demonstration project, we developed a system for 16 small rural hospitals to report, benchmark, and learn from fall events, and we trained them to conduct post-fall huddles. To calculate a hospital's repeat fall rate, we divided the total number of falls reported by the hospital by the number of unique medical record numbers associated with each fall. We used Spearman correlations with exact P values to determine the association between the proportion of falls followed by a huddle and the repeat fall rate. At study end, we used the TeamSTEPPS® Teamwork Perceptions Questionnaire (T-TPQ) to assess perceptions of teamwork support for fall-risk reduction and the Hospital Survey on Patient Safety Culture (HSOPS) to assess perceptions of safety culture. We added an item to the T-TPQ for respondents to indicate the number of post-fall huddles in which they had participated. We used a binary logistic regression with a logit link to examine the effect of participation in post-fall huddles on respondent-level percent positive T-TPQ and HSOPS scores. We accounted for clustering of respondents within hospitals with random effects using the GLIMMIX procedure in SAS/STAT. Result Repeat fall rates were negatively associated with the proportion of falls followed by a huddle. As compared to hospital staff who did not participate in huddles, those who participated in huddles had more positive perceptions of four domains of safety culture and how team structure, team leadership, and situation monitoring supported fall-risk reduction. Conclusions Post-fall huddles may reduce the risk of repeat falls. Staff who participate in post-fall huddles are likely to have positive perceptions of teamwork support for fall-risk reduction and safety culture because huddles are a team-based approach to reporting, adapting, and learning.